2023
DOI: 10.3389/fped.2023.1142069
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to antibiotics and risk of atopic dermatitis in childhood: a systematic review and meta-analysis

Abstract: BackgroundAlthough the association between maternal exposure to antibiotics and the risk of atopic dermatitis (AD) in childhood has been studied extensively, there still is a lack of clarity on the topic. The aim of this study was to summarize the published data and to examine if maternal exposure to antibiotics increases the risk of AD in childhood.MethodsSystematic search was performed in PubMed, Scopus, Web of Science, and Embase for all types of studies on the review subject independent of any language res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…There has been some evidence from meta-analyses for the link between antibiotic use in pregnancy (n = 18 studies) 57 and early life (n = 22 studies) 58 and infant AD. These studies varied considerably in design, ranging from cohort studies to case-control studies and retrospective medical record reviews, yielding high heterogeneity.…”
Section: Antib I Oti C Us E and S K In Microb Iomementioning
confidence: 99%
See 1 more Smart Citation
“…There has been some evidence from meta-analyses for the link between antibiotic use in pregnancy (n = 18 studies) 57 and early life (n = 22 studies) 58 and infant AD. These studies varied considerably in design, ranging from cohort studies to case-control studies and retrospective medical record reviews, yielding high heterogeneity.…”
Section: Antib I Oti C Us E and S K In Microb Iomementioning
confidence: 99%
“…Wan et al 57 in particular showed that significant links were demonstrated only for retrospective studies but not for prospective or cross-sectional studies, suggesting that a degree of ascertainment bias may exist. Confounding by indication may also be present in studies where the indication for antibiotic prescriptions may be due to early skin disease or infections.…”
Section: Antib I Oti C Us E and S K In Microb Iomementioning
confidence: 99%
“…There is a higher likelihood of childhood AD observed in cases where mothers used antibiotics during pregnancy [ 140 ]. In utero exposure to antibiotics, regardless of trimester, has been proven to raise the risk of eczema by 38%, with a more pronounced effect noted in children exposed to penicillin [ 141 , 142 ]. Yamamoto-Hanada et al discovered that the notable connection to eczema was primarily influenced by the use of macrolides [ 143 ].…”
Section: Microbiota As a Mediator Of Atopic Dermatitismentioning
confidence: 99%
“…Yamamoto-Hanada et al discovered that the notable connection to eczema was primarily influenced by the use of macrolides [ 143 ]. Studies have shown positive associations between exposure to antibiotics and AD, especially within the first year of life [ 136 , 142 , 143 ]. Postnatal antibiotic exposure in infants is also associated with an increased risk (40–80%) of developing atopic eczema [ 122 , 141 ].…”
Section: Microbiota As a Mediator Of Atopic Dermatitismentioning
confidence: 99%